THE IMPORTANCE OF A TRANSFORMATIONAL LEADERSHIP MODEL IN MANAGING ORGANIZATIONAL CULTURE - Salsabiila Astari Putri; Alif Mirzania; Dody Hartanto (Universitas Gadjah Mada, 2020)
In today's world conditions, everything can change very quickly. Change management is a series of systematic and complex processes that must be carried out by an organization to survive. Changes in the organization must be able to be managed properly to achieve the goals desired by the organization. Besides that, the organization as a complex unit also consists of various cultures. In this case, one of the right steps, so that management of organizational change can be managed properly, is by determining change leaders with transformational leadership models. Through review journals, a significant positive relationship between transformational leadership and the management of change within the organization will be presented.